Examining the Relationship Between Ambivalence Over Emotional Expressiveness and Suicidal Ideation in Veterans: The Mediating Role of PTSD Symptoms - Heshmati, Rasoul; Alizadeh, Dena; Al-Dujaili, Murtadha Abd Salman (International Journal of Education and Cognitive Sciences, 2026)
Purpose: This study aimed to examine the relationship between ambivalence over emotional expressiveness and suicidal ideation in veterans, with posttraumatic stress disorder (PTSD) symptoms considered as a mediating variable. Methods and Materials: This descriptive-correlational, cross-sectional study included 100 Iran–Iraq War veterans hospitalized at Fajr Hospital who were recruited through convenience sampling. Participants completed the Ambivalence over Emotional Expressiveness Questionnaire, the Beck Scale for Suicide Ideation, and the Mississippi Scale for Combat-Related PTSD. Pearson’s correlation was used to examine relationships among the variables. Structural equation modeling with maximum likelihood estimation was conducted in Mplus version 8 to test the mediation model. Normality was assessed using skewness and kurtosis, and multicollinearity was evaluated through variance inflation factors. Model fit was assessed using the chi-square-to-degrees-of-freedom ratio, comparative fit index, Tucker–Lewis index, and root-mean-square error of approximation. Bootstrapping was used to test the indirect effect. Findings: Suicidal ideation was significantly correlated with ambivalence over emotional expressiveness and PTSD symptoms. Ambivalence over emotional expressiveness significantly predicted suicidal ideation in the model without the mediator. In the mediation model, ambivalence over emotional expressiveness significantly predicted PTSD symptoms, and PTSD symptoms significantly predicted suicidal ideation. However, the direct path from ambivalence over emotional expressiveness to suicidal ideation was not statistically significant after PTSD symptoms were entered into the model. The indirect effect of ambivalence over emotional expressiveness on suicidal ideation through PTSD symptoms was statistically significant. The structural model demonstrated acceptable fit to the data. Conclusion: PTSD symptoms fully mediated the relationship between ambivalence over emotional expressiveness and suicidal ideation, suggesting that interventions targeting emotional-expression conflicts and trauma-related symptoms may help reduce suicidal ideation among veterans.